EXPLORING TEACHER KNOWLEDGE, CHALLENGES, AND PRACTICES IN PRESCHOOLERS’ SOCIAL AND EMOTIONAL DEVELOPMENT - Anis Sakinah Ahmad; Hairul Nizam Ismail; Mohd Ridzuan Mohd Taib (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study explores the knowledge, practices, and challenges preschool educators in Kedah, Malaysia, encounter when assessing children’s social and emotional development. Data from structured questionnaires filled out by 47 teachers provide important insights: Despite the fact that 65% of educators claim to be confident in their ability to assess students, 50% claim to lack culturally relevant resources, 42% claim to be time-constrained, and 35% point to a lack of chances for professional growth. Preschool teachers have limited access to culturally relevant tools and the time to implement them, along with challenges surrounding their own professional development needs, all of which combine to inhibit their capacity to support children’s holistic social and emotional development appropriately. This study seeks to overcome these limitations in order to enhance and advance the holistic development of preschoolers through early childhood education.